Mapping of data communication networks on social media - Noviar Jamaal Kholit; Muhamad Nastain (IAIN Salatiga, 2020)
Information technology is developing very fast, this has an impact on real changes in every element of life. In addition to hitting the information media industry, developments in information technology have brought updates to public spaces with easy access and an increasingly massive pattern of information distribution. Ease of access does not always present a positive side but there is a negative side, namely shifting communication patterns with the spread of false information or disinformation methods that invite public upheaval. This research uses the case study method, which is one way to investigate contemporary phenomena in the context of real life, where the boundaries between the phenomenon and the context are not clearly visible. Through the Social Network Analyzer (SNA) theoretical approach, this research will find three communication network patterns, namely a centralized network, a decentralized network and a distributed network.